Northrop Frye and Others : The Order of Words - Denham, Robert D (University of Ottawa Press, 2015)
"This book, based on extensive archival and historical work, identifies and brings to light additional and little recognized intellectual influences on Frye, and analyzes how they informed his thought. These are variously major thinkers, sets of texts, and intellectual traditions: the Mahayana Sutras, Machiavelli, Rabelais, Boehme, Hegel, Coleridge, Carlyle, Mill, Jane Ellen Harrison and Elizabeth Fraser. In each chapter, dedicated to Frye's connection to a specific influence, Denham describes how Frye became acquainted with each, and how he interpreted and adapted certain ideas from them to help work out his own conceptual systems. Denham offers insights on Frye's relationship with his historical and intellectual contexts, provides valuable additional context for understanding the work of one of the 20th century's leading scholars of literature and culture. Includes over 20 photos, tables and figures, as well as a chapter on Frye's personal relationship with Elizabeth Fraser."-- Provided by publisher.
Keywords: Frye, Northrop -- Criticism and interpretation.; Frye, Northrop; Criticism.; Influence (Literary, artistic, etc.); Critique.; Influence littéraire, artistique, etc.; criticism.; literary criticism.; LITERARY CRITICISM -- Semiotics & Theory.; Criticism; Criticism, interpretation, etc.